Peranan Perbankan Terhadap Perkembangan Lembaga Keuangan Mikro di Kota Tebing Tinggi - Muhammad Taufiq Assyauri Sidadolog; Coki Ahmad Syahwier (Ekonomi dan Keuangan, 2013)
This study aimed to determine the role of banking on the development of microfinanace institutions in Tebing Tinggi. Also to know how to influence lending rates, lending process, the number of credits the bank’s desicion on the loan request in Tebing Tinggi. Availability of funds given MFI banking is one indicator that banks have an influence in the development of microfinance institutions. In this study, the research object is the Microfinance institutions in Tebing Tinggi. With a sample of 40 respondens where sampling is population sampling. The test data where then analyzed using questionnaires statistical analysis such as the validity ang reliability test and descriptive statistics. The test result show that the interst rate, the loan and the amount of loans affect credit demand decisions on the banks operating in the City of High Cliff. This is evident from the test result obtained by the mean value of the variable interest rate is equal to 3.93, 4.11 for the loan, the amount of credit of 4.084. All items are in the range of variables statement score from 3.7 to 4.5 which means that all variables in this study influence decisions of the demand for credit in the banking system in Tebing Tinggi.Keywords : Banking, MFI, Lending Rate, Credit Supply Process, Credit Amount and Credit Demand Decisions.